If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(z + 1) + -1(5z + -4) = 0 Reorder the terms: 2(1 + z) + -1(5z + -4) = 0 (1 * 2 + z * 2) + -1(5z + -4) = 0 (2 + 2z) + -1(5z + -4) = 0 Reorder the terms: 2 + 2z + -1(-4 + 5z) = 0 2 + 2z + (-4 * -1 + 5z * -1) = 0 2 + 2z + (4 + -5z) = 0 Reorder the terms: 2 + 4 + 2z + -5z = 0 Combine like terms: 2 + 4 = 6 6 + 2z + -5z = 0 Combine like terms: 2z + -5z = -3z 6 + -3z = 0 Solving 6 + -3z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -3z = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -3z = 0 + -6 -3z = 0 + -6 Combine like terms: 0 + -6 = -6 -3z = -6 Divide each side by '-3'. z = 2 Simplifying z = 2
| (19b-6)-9(2b+4)=-2 | | 2(2)y+1=(2)y+3 | | 9x-8=16x+27 | | 12x+2.6=6.8x | | 54=3y+x | | 54=3x+y | | 2(x+9)=30+18 | | (19+3)2=x | | 5/4k=5 | | 54-3(45)= | | 5-2(4x-2)+2x= | | xa+5=7x+b | | -9(x+4)+2x+5=6x+11 | | Y=3*X+2 | | 3(45)+x+6(45)+4x=180 | | 4xy+5xy-3xz-2xy+xy+3xz= | | 8x+6-9x=2-y-15 | | 8-10p+4+8p= | | z(3+2i)=iz+2 | | 2(x+5)+5=2x+9 | | 3x-250=2858 | | 2x+15=385/(x+1) | | 3x+54-3x+6x+4(54-3x)= | | (x+3)(x^2+2x+6)=0 | | 1/16x-3/4y=-1 | | 5b-3/3b-4b+1/5b | | .2y+.5x=4.05 | | 2/3n=-18 | | -12=.5x+x | | 3y+x=54 | | 2(x+8)=30+18 | | 3x+y=54 |